Hydrodynamic optimisation of an axisymmetric floating Oscillating Water Column type wave energy converter with an enlarged inner tube. (December 2020) - Gradowski, M.; Gomes, R.P.F.; Alves, M.
Abstract: Wave Energy Converters (WECs) that are classified as Floating Oscillating Water Columns (FOWCs) of point absorber type are designed to achieve resonance, at frequencies that are favourable for wave energy extraction. The resonance frequency of a FOWC type WEC is highly dependent on the added mass of its OWC, which often requires a long spar tube to achieve well-performing hydrodynamics. A proposed measure for driving down the cost of the converter is to reduce its length, while finding another way of achieving the desired OWC added mass. Frequency-domain modelling and hydrodynamic optimisation of the Spar-buoy OWC was carried out for an enlarged spar tube segment inside the floater. Results are compared to those of buoys with equal spar and inner tube diameters. Frequency responses of optimised buoy geometries - with and without enlarged inner tubes - explore the differences in their hydrodynamics. Expanding the inner tube diameter of the Spar-buoy OWC may increase energy extraction by up to 6.7% and reduce the buoy mass by up to 11.4%, when operating in a Portuguese offshore location. A sensitivity analysis on mean annual pneumatic power to changes in inner tube diameter and spar tube length was performed. Highlights: Frequency and spectral-domain modelling of the Spar-buoy OWC was performed for an enlarged tube segment inside the floater. Frequency responses of optimised buoy geometries, with and without enlarged tubes, are presented. Capture width ratios, mean annual powers, and added masses of optimised buoys are presented. Tube expansion may increase energy extraction by up to 6.7% and reduce buoy mass by up to 11.4%. A sensitivity analysis on mean annual pneumatic power to changes in inner tube diameter and spar tube length was performed.